A A Displaying The Explanatory Factor Of Interest In Purchasing Luxury Villas In Bali By Foreign Citizen - Anasthasia, Arya Agung Ayu; Mahyuni, Mahyuni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims purchase interest is a behavior that arises in response to objects that indicate the desire of consumers to make purchases. Innovation is a new change that will lead to improvement. Then how can the property company convince investors in making purchases, if you look at from previous sales data in 2021 and 2023 there was a significant decline and increased significantly in 2024 in the sales process amid the property business competition in Bali. This study will use a qualitative approach with the case study analysis method. While the emergence of interest in the product is triggered by many aspects internally and externally. As a seller is very important to understand internal and internal aspects where it can help consumers feel the need to buy villas. Digital marketing is to describe the company's efforts to inform, promote, communicate and market a product and service through internet media. The role of architectural design innovation in increasing the interest of foreign investors towards the purchase of Luxury Villa in Bali is very significant. The emergence of competition in the business world is inevitable. With competition, efforts are faced with various opportunities and threats both from outside and from within the country. This study aims purchase interest is a behavior that arises in response to objects that indicate the desire of consumers to make purchases. Innovation is a new change that will lead to improvement. Then how can the property company convince investors in making purchases, if you look at from previous sales data in 2021 and 2023 there was a significant decline and increased significantly in 2024 in the sales process amid the property business competition in Bali. This study will use a qualitative approach with the case study analysis method. While the emergence of interest in the product is triggered by many aspects internally and externally. As a seller is very important to understand internal and internal aspects where it can help consumers feel the need to buy villas. Digital marketing is to describe the company's efforts to inform, promote, communicate and market a product and service through internet media. The role of architectural design innovation in increasing the interest of foreign investors towards the purchase of Luxury Villa in Bali is very significant. The emergence of competition in the business world is inevitable. With competition, efforts are faced with various opportunities and threats both from outside and from within the country.